Phase III PAOLA-1/ENGOT-ov25 trial: olaparib plus bevacizumab as maintenance therapy in patients with newly diagnosed, advanced ovarian cancer treated with platinum-based chemotherapy plus bevacizumab. (1st November 2019) - Harter, P; Mouret-Reynier, MA; Pignata, S; Cropet, C; González-Martin, A; Bogner, G; Fujiwara, K; Vergote, I; Colombo, N; Mäenpää, J; Floquet, A; El-Balat, A; et al.
Abstract : Introduction/Background: In the Phase III SOLO1 first-line trial, maintenance therapy with the PARP inhibitor olaparib provided a substantial progression-free survival (PFS) benefit to advanced ovarian cancer (OC) patients who have a BRCA1/2 mutation ( BRCA m) and are in complete or partial response to first-line chemotherapy (Moore K et al. N Engl J Med 2018). VEGF inhibitor may increase PARP sensitivity, particularly in some OC patients with BRCA wild type (Liu JF et al. Lancet Oncol 2014). PAOLA-1/ENGOT-ov25 (NCT02477644 ) is the first Phase III trial to evaluate the efficacy and safety of a PARP inhibitor with bevacizumab as first-line maintenance therapy, and in patients regardless of BRCA m status. Methodology: PAOLA-1 is a randomized, double-blind, international Phase III trial. Eligible patients had newly diagnosed, advanced (FIGO stage IIIA-IV) high-grade serous or endometrioid ovarian, fallopian tube or peritoneal cancer. Patients had no evidence of disease or were in partial response following first-line platinum-based chemotherapy plus bevacizumab. Bevacizumab was to be given for up to 15 months, including the initial combination with chemotherapy. 806 patients were randomized (2:1) in maintenance therapy to olaparib (300 mg bid) or placebo plus bevacizumab (15 mg/kg, d1, q3w), stratified by first-line treatment outcome and tumour BRCA m status. The primary endpoint is investigator-assessed PFS (modified RECIST v1.1). The 458 PFS events required for the primary analysis to show significance at the two-sided 5% level with an estimated >80% power have been reached in March 2019. Database lock was in July and analyses are ongoing. Results: The LBA will report: investigator-assessed PFS, PFS by BRCA m/HRD status, health- related quality of life, and safety and tolerability results. Conclusion: PAOLA-1 will demonstrate whether addition of olaparib to bevacizumab maintenance therapy following first-line platinum-based chemotherapy plus bevacizumab provides a clinically meaningful benefit to OC patients. Disclosure: P Harter declares honoraria from AstraZeneca, Roche, Sotio, Tesaro, Stryker, ASCO, Zai Lab and MSD; and consultancy/advisory board fees from AstraZeneca, Roche, Tesaro, Lilly, Clovis, Immunogen and MSD/Merck. Marie Ange Mouret-Reynier declares no conflicts of interest. S Pignata declares honoraria from Roche, AstraZeneca, MSD, Pfizer, Incyte, Novartis, PharmaMar, Clovis and Tesaro; and travel expenses from Roche, AstraZeneca and MSD. Claire Cropet declares no conflicts of interest. A Gonzalez-Martin declares consulting/advisory board fees from Roche, AstraZeneca, Tesaro, Clovis, Pfizer, ImmunoGen, PharmaMar, MSD, Genmad and Novartis; and speaker bureau/expert testimony fees from Roche, AstraZeneca, MSD Tesaro and PharmaMar. Gerhard Bogner declares consulting/advisory board fees from AstraZeneca Tesaro and Roche; and travel expenses from GSK, Roche, Pharmamar, AstraZeneca and Tesaro. K Fujiwara declares honoraria from AstraZeneca, Chugai Roche, Zeria, Taiho, Nihon Kayaku, Kyowahakko Kirin, Janssen and Daiichi Sankyo; consulting/advisory board fees from Pfizer, MSD and Eisai; research funding from AstraZeneca, MSD, Chugai Roche, Eisai and Kaken; and travel expenses from Pfizer. I Vergote declares consulting/advisory board fees from Advaxis, BIOCAD, Eisai, MSD, Roche, Genmab, Roche, PharmaMar, Millenium Pharmaceuticals, Clovis, AstraZeneca, Tesaro, Oncoinvent, ImmunoGen and Sotio; contracted research with Oncoinvent and Genmab; research funding from Amgen, Roche and Stichting tegen Kanker; and Takeda Oncology, PharmaMar, Genmab, Roche, AstraZeneca, Tesaro, Clovis and Immunogen. N Colombo declares honoraria from Roche, AstraZeneca, PharmaMar, Tesaro, Clovis, Pfizer, MSD, BIOCAD and Takeda; consulting/advisory board fees from Roche, AstraZeneca, PharmaMar, Tesaro, Clovis, Pfizer, MSD, BIOCAD, Takeda; and travel expenses from PharmaMar, Tesaro and Roche. J Mäenpää declares honoraria from Roche, AstraZeneca and Tesaro; consultancy/advisory board fees from AstraZeneca, Tesaro, Clovis and MSD; and travel expenses from Roche. Anne Floquet declares consultancy/advisory board fees from GSK, AstraZeneca and Clovis; and travel expenses from Roche, GSK and AstraZeneca. Ahmed El-Balat declares honoraria from AstraZeneca, Roche, Pharmamar, MSD, Tesaro, Clovis; and consultancy/advisory board fees from AstraZeneca and Roche. D Lorusso declares honoraria from Merck; consultancy/advisory board fees from Merck, AstraZeneca, Tesaro, Clovis, Immunogen, PharmaMar and Roche; research funding from Clovis, PharmaMar, Merck and Roche; and travel expenses from Tesaro, Roche and PharmaMar. EM Guerra Alia declares consultancy/advisory board fees from Roche, Clovis and AstraZeneca; and travel expenses from Roche and Baxter. Michel Fabro declares honoraria from Tesaro and AstraZeneca; and consultancy/advisory board fees from Tesaro and AstraZeneca. Barbara Schmalfeldt declares honoraria from Roche, AstraZeneca, Tesaro, Clovis, Ethicon, MSD; consultancy/advisory fees from Roche, AstraZeneca, Tesaro, Clovis, Ethicon, MDS; speaker bureau/expert testimony fees from Roche, AstraZeneca, Tesaro, Clovis, Ethicon, MDS; research grant funding from Roche, AstraZeneca, Tesaro, Clovis, Ethicon, MDS and travel expenses from Roche, AstraZeneca, Tesaro, Clovis, Ethicon, MDS. Anne Claire Hardy Blessard declares honoraria from AstraZeneca, Lilly, Novartis, Pfizer, Roche and Tesaro. Ingo Runnebaum declares honoraria from AstraZeneca. I Ray-Coquard declares honoraria from AstraZeneca, Clovis, Tesaro and PharmaMar; consulting/advisory board fees from AstraZeneca, Roche, Clovis, Tesaro, Genmab, PharmaMar, MSD and Pfizer; research funding from MSD; and travel expenses from AstraZeneca and Roche; consulting/advisory board fees from Roche; and travel expenses from Roche, MSD, Tesaro and AstraZeneca. E Pujade-Lauraine declares honoraria from AstraZeneca and Tesaro; consulting/advisory board fees from AstraZeneca, Roche, Clovis, Tesaro, Genmab, Incyte, MSD and Pfizer; research funding from AstraZeneca, Roche and Tesaro; and travel expenses from AstraZeneca, Roche and Tesaro.